The Effect of Physical Work Environment and Compensation on Turnover Intention With Job Satisfaction Mediation at PT Pakubumi Inti Mineral Central Sulawesi - Nurhayati; Rachman, Taufiq; Rezeki, Fitri (Dinasti Publisher, 2024)
The human resources (HR) element plays a crucial role for employees to act as planners, implementers, and controllers, continuously playing an active role in achieving the company's goals. Productive human resources will be able to adopt designs that are set as organizational goals or targets. This phenomenon often occurs in companies where employees have the desire to leave the company. The focus of this research is on PT Pakubumi Inti Mineral in Central Sulawesi, examining the Influence of Physical Work Environment and Compensation on Turnover Intention with the Mediation of Job Satisfaction. The research method used is quantitative, distributing questionnaires that were then processed using the SmartPLS 3.0 application. The results of the study show that both the physical work environment and compensation have a positive and significant impact on employee turnover intention, with compensation showing a stronger and more significant influence. Job satisfaction also plays a significant mediating role between compensation and turnover intention, but not in the case of the physical work environment.